Target Price Accuracy - Alexander G. Kerl (BuR - Business Research, 2011)
This study analyzes the accuracy of forecasted target prices within analysts reports. We compute a measure for target price forecast accuracy that evaluates the ability of analysts to exactly forecast the ex-ante (unknown) 12-month stock price. Furthermore, we determine factors that explain this accuracy. Target price accuracy is negatively related to analyst-specific optimism and stock-specific risk (measured by volatility and price-to-book ratio). However, target price accuracy is positively related to the level of detail of each report, company size and the reputation of the investment bank. The potential conflicts of interests between an analyst and a covered company do not bias forecast accuracy.
urn:nbn:de:0009-20-29788
Keywords: 650; analyst report; conflicts of interest; efficient capital markets; equity analysis; financial report; forecast accuracy; forecast deviation; information content; security analysis; target prices; Börsenkurs; Finanzanalyse; Prognoseverfahren; Kapitaleinkommen; Erfolgsfaktor